Chikusetsusaponin V inhibits inflammatory responses via NF-κB and MAPK signaling pathways in LPS-induced RAW 264.7 macrophages. (December 2014) - Wang, Ting; Dai, Yanwen; Dun, Yaoyan; Zhang, Changcheng; Wan, Jingzhi; Deng, Lili; Zhou, Zhiyong; Liu, Chaoqi; Yuan, Ding
Abstract Excessive activation of macrophages is implicated in various inflammation resulted injuries. Saponins from Panax japonicus (SPJ) have been shown to possess anti-inflammatory activities. However, whether Chikusetsusaponin V (CsV), the most abundant component of SPJ, can exert anti-inflammatory activities is unknown. The present study was aimed to investigate the anti-inflammatory effects of CsV in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells and the underlying mechanisms. Our data showed that CsV dose-dependently inhibited NO, iNOS, TNF-α and IL-1β expressions in LPS-stimulated RAW264.7 cells. Increased protein levels of nuclear NF-κB and elevated phosphorylation levels of ERK and JNK in LPS-stimulated RAW 264.7 cells were also found downregulated by CsV treatment. Furthermore, the increase of CD14 and TLR4 mRNA expression due to LPS stimulation were significantly reversed by CsV treatment. These results suggested that CsV attenuated LPS-induced inflammatory responses partly via TLR4/CD14-mediated NF-κB and MAPK pathways.